Nutrient use efficiency in sugarcane cultivars - Kist, Volmir; Silveira, Gustavo da; Costa, Paulo Mafra de Almeida; Oliveira, Mauro Wagner de; Barbosa, Márcio Henrique Pereira (Científica, 2015)
This work aimed at assessing the nutritional efficiency of sugarcane cultivars in plant and first ratoon crop cycles. Eight cultivars were evaluated for the characters nutrient content (N, P, K, Ca and Mg) accumulated in the leaf +3 (L+3) and in the biomass and productivity of dry matter (DM). Significant differences (p<0.05) between cultivars were observed in almost all variables. The cultivars were separated into two and three groups in function of the nutrient accumulated in L+3 and biomass, respectively, both in plant cane and first ratoon cane. The average productivity of DM was 38 t ha-1 and 27.8 t ha-1 in plant cane and first ratoon, respectively. Only the cultivar RB867515 showed high utilization efficiency for all nutrients accumulated in L+3 in the two cycles. On the other hand, any cultivar exhibited simultaneous high utilization efficiency in the five evaluated nutrients in biomass. The cultivar that showed the best utilization efficiency was RB835486, standing out in four nutrients (N, P, Ca and Mg) in the two cycles. However, it was not possible to identify the best cultivars based only on nutrient utilization efficiency.